2012
DOI: 10.1042/bj20120060
|View full text |Cite
|
Sign up to set email alerts
|

CD36 inhibition prevents lipid accumulation and contractile dysfunction in rat cardiomyocytes

Abstract: An increased cardiac fatty acid supply and increased sarcolemmal presence of the long-chain fatty acid transporter CD36 are associated with and contribute to impaired cardiac insulin sensitivity and function. In the present study we aimed at preventing the development of insulin resistance and contractile dysfunction in cardiomyocytes by blocking CD36-mediated palmitate uptake. Insulin resistance and contractile dysfunction were induced in primary cardiomyocytes by 48 h incubation in media containing either 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
102
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 48 publications
9
102
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to revealed that both exendin‐4 and saxagliptin significantly reduced lipid content in CMs both in vivo and in vitro by controlling the PPARa‐CD36 pathway, which is a major regulatory signal in cardiac FA metabolism. The long‐chain FA transporter CD36 is responsible for >60% of the cardiac FA uptake (Angin et al., 2012). Heart‐specific CD36 deficiency prevents myocardial lipid accumulation and rescues cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to revealed that both exendin‐4 and saxagliptin significantly reduced lipid content in CMs both in vivo and in vitro by controlling the PPARa‐CD36 pathway, which is a major regulatory signal in cardiac FA metabolism. The long‐chain FA transporter CD36 is responsible for >60% of the cardiac FA uptake (Angin et al., 2012). Heart‐specific CD36 deficiency prevents myocardial lipid accumulation and rescues cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…1 , muscle cells did not exhibit an increase in proinfl ammatory signaling when chronically exposed to oleate, a very prevalent circulating MUFA. Furthermore, like palmitoleate, oleate was able to attenuate the proinfl ammatory effects of both palmitate and stearate based on the reduced phosphorylation of loss of I B ␣ in L6 myotubes, both events were noticeably reduced in muscle cells that had been preincubated with anti-CD36 at concentrations previously reported to inhibit CD36-mediated fatty acid uptake ( 36 ). Antibody treatment did not modify palmitoleate action, consistent with the idea that the ability of this MUFA to repress the proinfl ammatory effect of palmitate was contingent on cellular fatty acid uptake.…”
Section: Palmitate Induces Rkip Phosphorylation and Its Dissociation mentioning
confidence: 94%
“…1 and 2 may be initiated by signaling cascades that start at the cell membrane and do not require palmitate to enter the cell. To test this possibility, we investigated the effects of an antibody that inhibits palmitate uptake via the CD36 fatty acid transporter ( 36 ). Fig.…”
Section: Do Dag and Dag-sensitive Pkcs Play A Role In Palmitateinducementioning
confidence: 99%
“…CD36 Ϫ/Ϫ mice are protected from myocardial dysfunction consequent to excessive FA supply or impaired mitochondrial capacity, suggesting that targeting CD36 may be beneficial under these conditions (15)(16)(17)(18)(19). Conversely, CD36 deficiency eliminates the fuel flexibility that is characteristic of the healthy myocardium (20), and whether this impacts myo-cardial capability to adapt to certain stresses remains unknown.…”
mentioning
confidence: 99%